Analysis of Tar Properties Produced During Co-Gasification of Empty Fruit Bunch Pellet and Oil Palm Shell - Ramli, Amir Zuhairi; Sabudin, Sulastri; Mohideen Batcha, Mohd Faizal; Waehahyee, Makatar (International Journal of Integrated Engineering, 2020)
In this study, tar produced during co-gasification of empty fruit bunch pellet (EFBP) and oil palm shell (OPS) was analyzed. The aim of the analysis is to characterize tar samples with three different fuel composition of 100% EFBP:0% OPS, 75% EFBP:25% OPS and 50% EFBP:50% OPS. Two types of analysis were carried out, namely the physical and chemical analysis. Physical analysis determines the moisture content, density and calorific value of tar samples while the chemical analysis via Fourier Transform Infrared (FTIR) Spectroscopy determines the functional group in the tar samples. In general, it was found the moisture content, density and calorific value increases with higher amount of OPS in the fuel mixture. The calorific value ranges from 4.722 MJ/kg to 21. 877 MJ/kg whiles the moisture content and the density ranges from 30.90% to 47.20% and 2.74089 g/cm3 to 2.99075 g/cm3. From FTIR analysis, it was found the tar contains alcohol, carbonyl, alkene, aromatic, ether and nitro. This corresponds to the characteristic absorptions during FTIR, which were 3200cm-1 to 3600cm-1 (O-H), 1670cm-1 to 1820cm-1 (C=O), 1620cm-1 to 1680cm-1 (C=C), 1400cm-1 to1600cm-1 (C=C), 1000cm-1 to 1300cm-1 (C-O) and 1345cm-1 to 1385cm-1 (N-O).